KAJIAN MUSAWARAH : CONTEMPORARY DA’WAH, PIOUS IDENTITY AND VIRTUAL UMMAH - Fathayatul Husna Yusri (Islam Futura, 2021)
This article analyzes the emergence of contemporary Islamic movement in Indonesia, especially in Kajian Musawarah community that massively do da’wah from hijrah celebrity group. Da’wah movement will be blossom through technology movement. This article examines how popularity as part to drive contemporary da’wah. This study important to see how celebrities position themselves as a new religion authority that evoke the spirit of contemporary da’wah, both online and offline. Besides, this article 5also to see how hijrah celebrity popularity appears as piety identity. This study also examines how new media unite all Muslim through imagined community. This article was made through observation on Instagram and youtube Kajian Musawarah and also supported with literature studies. The result of this study shows that hijrah celebrity popularity supports appearing da’wah movement in a celebrity group. Besides, Kajian Muswarah encourages the formation of virtual umma and imagined communities through new media.